Titanium niobate material rich in fault defect as well as preparation method and application of titanium niobate material
By introducing layer fault defects into titanium niobate materials, the problem of insufficient electrochemical performance of TNO materials is solved, efficient modification of the material is achieved, suitable for large-scale production, and the electrochemical performance of the negative electrode material of lithium-ion battery is significantly improved.
Patent Information
- Application Number
- CN202411763134.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-03
- Publication Date
- 2025-03-07
AI Technical Summary
In the prior art, the commercial application of TiNb2O7 (TNO) as a negative electrode material for lithium-ion batteries is limited by its relatively low intrinsic electron conductivity and slow ion transfer, and the modification methods are cumbersome and the equipment requirements are high, so it is not suitable for large-scale production.
The quenching technology introduces layer fault defects into the crystal structure of the titanium niobate material. The specific steps include dissolving the titanium source and the niobate source in an organic solvent, performing a solvothermal reaction to form a precursor, and then undergoing heat treatment and quenching treatment to form a layer fault defect-rich titanium niobate material.
It significantly reduces the bandwidth of TNO, improves the ionic conductivity and electronic conductivity of the material, improves the electrochemical performance, reduces the impedance, increases the Li+ diffusion coefficient, is suitable for large-scale production, and improves the cycling and rate performance of the negative electrode material of lithium-ion battery.
Smart Images

Figure CN119581544A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of energy storage materials, relates to lithium ion battery electrode materials, and specifically relates to a titanium niobate material rich in stacking fault defects, a preparation method and an application thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] In recent decades, rechargeable lithium-ion batteries have been widely used in electric vehicles and portable electronic devices due to their environmental friendliness, long service life, and high energy density. Graphite, as the most commercialized negative electrode material for lithium-ion batteries, has the advantages of long service life and high energy density. However, due to the low working potential of graphite (<0.1V vs Li + / Li), the lithium dendrites generated on the surface can pierce the separator, causing safety issues. In contrast, the high lithium insertion potential (1.5V vs Li + / Li) 12 (LTO) can simultaneously prevent the formation of lithium dendrites, ensuring cycle life and safety. Unfortunately, only 175mA hg -1 Theoretical capacity makes its energy density low.
[0004] TiNb2O7(TNO), due to its relatively high redox voltage (1.64V vs Li + / Li) and the presence of three redox pairs (Nb 5+ / Nb 4+ , Nb 4+ / Nb 3+ and Ti 4+ / Ti 3+ ) makes it twice the theoretical capacity of LTO (387.6mAh g -1 ) has become the most ideal substitute for LTO. However, the relatively low intrinsic electronic conductivity and slow ion transfer of TNO still hinder its commercial application.
[0005] At present, various modification methods have been applied to obtain TNO with better electrochemical properties, such as synthesis with highly conductive materials, control of morphology and particle size, etc. However, the above modification methods are relatively cumbersome, have too high requirements on equipment, and are not suitable for large-scale production. Among them, defect engineering is one of the most widely used modification methods, and has broad application prospects in improving the electronic conductivity of TNO and increasing the ionic conductivity of TNO. However, what kind of defects can improve the electrochemical performance of TNO, and how to simply and effectively introduce defects into TNO still needs to be explored. Summary of the invention
[0006] In order to solve the shortcomings of the prior art, the purpose of the present invention is to provide a titanium niobate material rich in stacking fault defects and its preparation method and application. The present invention introduces stacking fault defects into electrode materials, which can improve the electrochemical properties of electrode materials, reduce impedance, and increase Li + Diffusion coefficient.
[0007] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides a titanium niobate material rich in stacking fault defects, and the structure of the material is as follows: the crystal structure of the titanium niobate material contains at least one stacking fault defect, and the stacking fault defect is an atomic layer inserted into the normal crystal sequence of the titanium niobate material, and the stacking order of the atomic layer is different from that of the remaining atomic layers, so that two inversely stacked layers appear at this position.
[0008] The stacking fault defect is formed by inserting an atomic layer different from the surrounding sequence into the normal sequence through quenching technology. Specifically, at the stacking fault defect, two adjacent atomic layers are stacked in reverse order, thus breaking the original symmetry of the crystal.
[0009] The second aspect of the present invention provides a method for preparing the above-mentioned titanium niobate material rich in stacking fault defects, comprising:
[0010] Dissolving a titanium source and a niobium source in an organic solvent and stirring to obtain a mixed solution;
[0011] heating the mixed solution to perform a solvothermal reaction to generate a precursor;
[0012] The precursor is subjected to heat treatment and then quenching treatment to obtain a titanium niobate material with stacking faults; wherein the heat treatment temperature is 600-1000°C and the time is 2-8h.
[0013] The present invention performs quenching treatment on the precursor after heat treatment and introduces a stacking fault defect structure, which can significantly reduce the band gap width of the titanium niobate material TNO, improve the ionic conductivity and electronic conductivity of the material, and improve the electrochemical performance of TNO.
[0014] The present invention introduces stacking fault defects into TNO by quenching the precursor after heat treatment, which can effectively shorten its band gap and improve ion / electronic conductivity, thereby further improving its cycle performance and rate performance. First, TNO with nanoparticle morphology is prepared, and nanoparticles have a larger specific surface area, which is more conducive to Li + At the same time, selective quenching introduces defects into TNO, which increases the number of defects inside the crystal. Some defects, such as stacking faults, are beneficial to Li + The diffusion of ions improves the ionic conductivity of the material, and at the same time, shortens the band gap of the material and improves the electronic conductivity of the material.
[0015] In some embodiments, the addition ratio of the titanium source and the niobium source is: the molar ratio of Ti to Nb is 1:(1.9-2.1), preferably 1:(1.95-2.05).
[0016] In some embodiments, the titanium source includes one or more of titanium tetrachloride, butyl titanate, and isopropyl titanate.
[0017] In some embodiments, the niobium source includes one or more of niobium chloride and niobium oxalate.
[0018] In some embodiments, the organic solvent includes one or more of anhydrous ethanol, isopropanol, glycerol and ethylene glycol; preferably, a mixed solvent of ethylene glycol and isopropanol; further preferably, the volume ratio of ethylene glycol to isopropanol is (1-3): (3-1). By selecting different solvents, the particle size of the TNO nanoparticle negative electrode material can be adjusted.
[0019] In some embodiments, the reaction temperature of the solvothermal reaction is 120-200° C., and the reaction time is 6-48 h. Preferably, the reaction temperature is 140-200° C., and the reaction time is 12-36 h.
[0020] In some embodiments, the solvothermal reaction is carried out in a hydrothermal reactor.
[0021] In some embodiments, the precursor generated by the solvent thermal reaction is washed and dried, and then heat treated; preferably, the washing method includes one or more of filtration and centrifugation; preferably, the drying temperature is 80-120°C, and the drying time is 12-48h.
[0022] In some embodiments, the heat treatment is calcination, and the heating rate is 3-10°C / min; preferably, the calcination temperature is 700-900°C, the calcination time is 4-6h, and the heating rate is 4-8°C / min.
[0023] In some embodiments, calcination is performed in a rapid temperature ramp furnace.
[0024] In some embodiments, the quenching treatment is air quenching or liquid quenching; preferably, the liquid quenching is to quickly add the precursor calcined to the highest temperature into a coolant for cooling.
[0025] In some embodiments, the coolant used in the quenching treatment is air, distilled water, anhydrous ethanol or liquid nitrogen; preferably distilled water or liquid nitrogen; more preferably, the distilled water is liquid water at 0-25°C.
[0026] The third aspect of the present invention provides the use of the above-mentioned stacking fault defect-rich titanium niobate material or the stacking fault defect-rich titanium niobate material prepared by the above-mentioned preparation method of the stacking fault defect-rich titanium niobate material in lithium-ion battery negative electrode materials.
[0027] In a fourth aspect, the present invention provides a lithium-ion battery negative electrode, comprising a conductive substrate and the above-mentioned stacking fault defect-rich titanium niobate material or the stacking fault defect-rich titanium niobate material prepared by the above-mentioned method for preparing the stacking fault defect-rich titanium niobate material.
[0028] In a fifth aspect, the present invention provides a lithium ion battery, comprising the above-mentioned lithium ion battery negative electrode.
[0029] The beneficial effects of the present invention are:
[0030] 1. The present invention performs quenching treatment on the precursor after heat treatment, introduces a stacking fault defect structure, and can significantly reduce the band gap width of TNO. TNO is used as a negative electrode material to improve the electrochemical performance of the negative electrode, reduce impedance, and increase Li + Diffusion coefficient. At the same time, the solvothermal method is used to prepare the TNO precursor, which has a simple process and a low synthesis temperature. By changing the organic solvent and controlling the time, temperature and other reaction conditions of the solvothermal reaction, the reaction can be effectively controlled and the size of the nanoparticles can be adjusted.
[0031] 2. The preparation method of the modified material provided by the present invention is simple, does not introduce other impurities, and has low requirements on equipment. It is easy to commercially expand production and has a very high yield. At the same time, quenching can reduce the orderliness of the crystal and cause changes in the interplanar spacing. The obtained TNO nanoparticle negative electrode material rich in staggered defects has very excellent cycle performance and rate performance, and is expected to obtain more excellent electrochemical performance when applied to the negative electrode of lithium-ion batteries.
[0032] 3. The TNO provided by the present invention is applied to the negative electrode of lithium-ion batteries. The constant current charge and discharge, GITT and EIS and other electrochemical performance tests show that the electrochemical performance is improved, the impedance is reduced, and the Li+ diffusion coefficient is increased after the stacking fault is introduced by quenching. Therefore, the lithium ion / electron migration of the modified TNO by quenching and introducing stacking faults has a certain reference value for the defect engineering research of the new negative electrode, and provides a valuable application prospect for the commercialization of TNO. BRIEF DESCRIPTION OF THE DRAWINGS
[0033] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0034] Figure 1 The TNO nanoparticle negative electrode material with stacking fault defects prepared in Example 1 of the present invention is 0.2C (1C = 387.6mA g -1 ) under the cycle performance;
[0035] Figure 2 The figure is the rate performance of the TNO nanoparticle negative electrode material with stacking fault defects prepared in Example 3 of the present invention at different current densities;
[0036] Figure 3 1 is a high-resolution image (STEM-HAADF) of the spherical aberration of the TNO nanoparticle negative electrode material prepared in Comparative Example 1 and Example 4 of the present invention; wherein, (a) is a high-resolution image of the spherical aberration of the TNO nanoparticle negative electrode material prepared in Comparative Example 1, with a scale of 5 nm; (c) is an enlarged image of the yellow framed portion in (a), with a scale of 2 nm; (b) is a high-resolution image of the spherical aberration of the TNO nanoparticle negative electrode material prepared in Example 4, with a scale of 5 nm; (d) is an enlarged image of the yellow framed portion in (b), with a scale of 2 nm;
[0037] Figure 4 is a spectrum of the Ti(Nb) column in the HAADF-STEM micrograph of the TNO nanoparticle negative electrode material prepared in Comparative Example 1(a) and Example 4(b) of the present invention;
[0038] Figure 5 is an X-ray diffraction pattern (XRD) of the TNO nanoparticle negative electrode material with stacking fault defects prepared in Example 8 of the present invention;
[0039] Figure 6 3 are scanning electron microscope images of the TNO nanoparticle negative electrode material with stacking fault defects prepared in Example 10 of the present invention at different magnifications, wherein the scale bar of (a) is 2 μm; (b) is an enlarged view of the yellow framed portion in (a), and the scale bar is 1 μm. DETAILED DESCRIPTION
[0040] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used in the present invention have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.
[0041] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0042] The raw materials involved in the following examples are all common commercially available products.
[0043] Example 1
[0044] Use a balance to weigh the titanium source and niobium source and dissolve them in a mixed solvent of ethylene glycol: isopropanol with a ratio of 3:1, where the molar ratio of Ti:Nb is 1:1.95. After being fully mixed on a magnetic stirrer, transfer them to a hydrothermal reactor and react at 140°C for 12 hours. Wash and centrifuge the cooled precursor and dry it at 80°C for 24 hours. Finally, place the obtained precursor in a rapid heating furnace, heat it to 700°C at a rate of 5°C / min, calcine for 4 hours, take it out immediately and put it into distilled water at room temperature for rapid cooling, and obtain the final product titanium niobate after drying. Among them, the titanium source is tetrabutyl titanate and the niobium source is niobium chloride.
[0045] Example 2
[0046] Use a balance to weigh the titanium source and niobium source and dissolve them in a mixed solvent of ethylene glycol: isopropanol with a ratio of 2:1, where the molar ratio of Ti:Nb is 1:1.95. After being fully mixed on a magnetic stirrer, transfer them to a hydrothermal reactor and react at 160°C for 12 hours. Wash and filter the cooled precursor, and dry it at 80°C for 12 hours. Finally, place the obtained precursor in a rapid heating furnace, heat it to 700°C at a rate of 7°C / min, calcine for 4 hours, take it out immediately and put it into 2°C distilled water for rapid cooling, and obtain the final product after drying. Among them, the titanium source is titanium tetrachloride and the niobium source is niobium chloride.
[0047] Example 3
[0048] Use a balance to weigh the titanium source and niobium source and dissolve them in a mixed solvent of ethylene glycol: isopropanol with a ratio of 2:1, where the molar ratio of Ti:Nb is 1:2. After being fully mixed on a magnetic stirrer, transfer them to a hydrothermal reactor and react at 160°C for 12 hours. Wash and centrifuge the cooled precursor and dry it at 100°C for 24 hours. Finally, place the obtained precursor in a rapid heating furnace, heat it to 800°C at a rate of 4°C / min, calcine for 4 hours, take it out immediately and put it into 2°C distilled water for rapid cooling, and obtain the final product after drying. Among them, the titanium source is titanium tetrachloride and the niobium source is niobium chloride.
[0049] Example 4
[0050] Use a balance to weigh the titanium source and niobium source and dissolve them in a mixed solvent of 1:1 ethylene glycol: isopropanol, where the molar ratio of Ti:Nb is 1:2. After being fully mixed on a magnetic stirrer, transfer them to a hydrothermal reactor and react at 180°C for 24 hours. Wash and filter the cooled precursor, and dry it at 100°C for 12 hours. Finally, place the obtained precursor in a rapid heating furnace, heat it to 800°C at a rate of 5°C / min, calcine for 4 hours, take it out immediately and put it into 2°C distilled water for rapid cooling, and obtain the final product after drying. Among them, the titanium source is butyl titanate and the niobium source is niobium chloride.
[0051] Example 5
[0052] The titanium source and niobium source were weighed on a balance and dissolved in a mixed solvent of ethylene glycol: isopropanol with a molar ratio of Ti:Nb of 1:1. After being fully mixed on a magnetic stirrer, they were transferred to a hydrothermal reactor and reacted at 180°C for 24 hours. The cooled precursor was washed and centrifuged and dried at 100°C for 24 hours. Finally, the obtained precursor was placed in a rapid heating furnace, heated to 900°C at a rate of 5°C / min, and immediately taken out and placed in liquid nitrogen for rapid cooling after calcination for 4 hours, and the final product was obtained after drying. Among them, the titanium source is butyl titanate and the niobium source is niobium chloride.
[0053] Example 6
[0054] Use a balance to weigh the titanium source and niobium source and dissolve them in a mixed solvent of ethylene glycol: isopropanol with a ratio of 1:2, where the molar ratio of Ti:Nb is 1:1.98. After being fully mixed on a magnetic stirrer, transfer them to a hydrothermal reactor and react at 160°C for 24 hours. Wash and filter the cooled precursor, and dry it at 100°C for 24 hours. Finally, place the obtained precursor in a rapid heating furnace, heat it to 700°C at a rate of 7°C / min, calcine for 3 hours, immediately take it out and put it into liquid nitrogen for rapid cooling, and then dry it to obtain the final product. Among them, the titanium source is butyl titanate and the niobium source is niobium chloride.
[0055] Example 7
[0056] Weigh the titanium source and niobium source on a balance and dissolve them in a mixed solvent of ethylene glycol: isopropanol with a ratio of 1:2, where the molar ratio of Ti:Nb is 1:2.02. After being fully mixed on a magnetic stirrer, transfer them to a hydrothermal reactor and react at 180°C for 24 hours. Wash and centrifuge the cooled precursor and dry it at 120°C for 24 hours. Finally, place the obtained precursor in a rapid heating furnace, heat it to 900°C at a rate of 5°C / min, calcine for 4 hours, take it out immediately and put it into distilled water at room temperature for rapid cooling, and obtain the final product after drying. Among them, the titanium source is butyl titanate and the niobium source is niobium oxalate.
[0057] Example 8
[0058] Weigh the titanium source and niobium source on a balance and dissolve them in a mixed solvent of ethylene glycol: isopropanol with a ratio of 1:3, where the molar ratio of Ti:Nb is 1:2. After being fully mixed on a magnetic stirrer, transfer them to a hydrothermal reactor and react at 200°C for 24 hours. Wash and centrifuge the cooled precursor and dry it at 100°C for 24 hours. Finally, place the obtained precursor in a rapid heating furnace, heat it to 800°C at a rate of 4°C / min, calcine for 4 hours, take it out immediately and put it into liquid nitrogen for rapid cooling, and obtain the final product after drying. Among them, the titanium source is butyl titanate and the niobium source is niobium chloride.
[0059] Example 9
[0060] Use a balance to weigh the titanium source and niobium source and dissolve them in a mixed solvent of ethylene glycol: isopropanol with a ratio of 1:3, where the molar ratio of Ti:Nb is 1:2.05. After being fully mixed on a magnetic stirrer, transfer them to a hydrothermal reactor and react at 180°C for 36 hours. Wash and filter the cooled precursor, and dry it at 120°C for 24 hours. Finally, place the obtained precursor in a rapid heating furnace, heat it to 700°C at a rate of 5°C / min, calcine for 4 hours, take it out immediately and put it into 2°C distilled water for rapid cooling, and obtain the final product after drying. Among them, the titanium source is isopropyl titanate and the niobium source is niobium oxalate.
[0061] Example 10
[0062] Use a balance to weigh the titanium source and niobium source and dissolve them in a mixed solvent of ethylene glycol: isopropanol with a ratio of 1:2, where the molar ratio of Ti:Nb is 1:1.95. After being fully mixed on a magnetic stirrer, transfer them to a hydrothermal reactor and react at 160°C for 36 hours. Wash and filter the cooled precursor, and dry it at 80°C for 24 hours. Finally, place the obtained precursor in a rapid heating furnace, heat it to 800°C at a rate of 5°C / min, calcine for 4 hours, immediately take it out and put it into 2°C distilled water for rapid cooling, and obtain the final product after drying. Among them, the titanium source is butyl titanate and the niobium source is niobium chloride.
[0063] Comparative Example 1
[0064] The difference between this comparative example and Example 4 is that the quenching step is omitted, and the remaining steps are the same as those of Example 4.
[0065] Experimental test analysis
[0066] Assembly of half-cells: The TNO nanoparticles with stacking faults in Examples 1-10 were used as active materials, lithium sheets were used as counter electrodes, 5% polyvinylidene fluoride (PVDF) solution in N-methylpyrrolidone (NMP) was used as a binder, acetylene black was used as a conductive agent, Celgard 2300 diaphragm was used as a battery diaphragm, and 1 mol / L lithium hexafluorophosphate was dissolved in a mixture of ethyl carbonate and diethyl carbonate (volume ratio of 1:1) was used as an electrolyte. Half-cells were assembled in a glove box filled with argon protection and then tested.
[0067] Figure 1 The TNO material with stacking fault defects prepared in Example 1 of the present invention is used as a negative electrode active material, and the cycle performance diagram at a current density of 0.2C. It can be concluded that the capacity of the first charge and discharge is 263.9 / 334.9mA h / g, and the first coulomb efficiency is 80.67%. After 100 cycles, the discharge specific capacity can still be maintained at 244.5mAh / g. This shows that the TNO negative electrode material with stacking fault defects has excellent cycle performance.
[0068] Figure 2 The figure is a rate performance diagram of the TNO material with stacking fault defects prepared in Example 3 of the present invention as the negative electrode active material at different current densities. It can be seen that the capacity remains at 283.1, 263.7, 250.1, 234.5, 200.1 and 149.9 mAh / g at current densities of 0.2, 0.5, 1.0, 2.0, 5.0 and 10C, respectively, and finally returns to the current density of 0.2C, and the capacity is still as high as 260.4 mA h / g. This shows that the rate performance of the TNO nanoparticle negative electrode material with stacking fault defects has been significantly improved.
[0069] Figure 3 (a) is a high-resolution image of the spherical aberration of TNO nanoparticle negative electrode materials. Figure 3 (c) is a high-resolution image of the spherical aberration of TNO nanoparticle negative electrode material with stacking fault defects. Figure 3 The stacking fault phenomenon in (c) is particularly significant, and this stacking fault structure has a positive effect on improving the electrochemical performance of TNO negative electrode materials. Specifically, the existence of stacking fault defects is Li + The rapid insertion and extraction of the stacking fault provides a more convenient channel, thereby accelerating the electrochemical reaction process and improving the charge and discharge performance of the material. Therefore, the introduction of the stacking fault structure through quenching effectively improves its electrochemical performance as a negative electrode material.
[0070] In order to further reveal the specific morphology of this stacking fault structure, Fourier transform (FFT) analysis was performed on the HAADF-STEM image. The corresponding linear profile is shown in Figure 4As shown in the figure, compared with NC-TNO, the linear profile of IWC-TNO along
[003] has an extra layer of Ti(Nb) column in the interval originally formed by two layers of Ti(Nb) columns, which more intuitively illustrates that quenching breaks the original crystal structure. Specifically, the inserted atomic layer causes the two adjacent atomic layers to stack in reverse order, thereby breaking the original symmetry of the crystal and forming a stacking fault defect.
[0071] Figure 5 The X-ray diffraction pattern (XRD) of the TNO material with stacking fault defects obtained in Example 8 of the present invention is shown in the figure. It can be seen from the figure that the diffraction peak of the material corresponds to the TNO standard PDF card (JCPDS No. 771374) and there are no other impurities.
[0072] Figure 6 This is a scanning image of the TNO material with stacking fault defects prepared in Example 10 of the present invention. It can be seen from the figure that the material is composed of nanoparticles with relatively uniform particle sizes. According to a rough estimate by XRD, the average particle size of the TNO material prepared in Example 10 after quenching is 10.8 nm; while the average particle size of the TNO material prepared in Comparative Example 1 without quenching is 17.5 nm, and the particle size is uneven.
[0073] The present invention uses a novel method of introducing defects, and the quenching technology successfully introduces stacking faults into the TNO crystal structure. This breakthrough brings new possibilities to the fields of materials science and nanotechnology. The basic principle of the quenching technology is to quickly cool the TNO crystal at a high temperature to room temperature or lower temperature, thereby suppressing the normal orderly arrangement of atoms inside the crystal, causing atomic layer misalignment in some areas. In this process, the rapid temperature change will cause thermal stress inside the crystal, causing the local lattice structure to distort, and then form stacking faults. Stacking faults, as a type of surface defect in the crystal, directly destroy the originally ordered atomic arrangement. In TNO, stacking faults may cause the stacking order between atomic layers to change, such as the appearance of abnormal stacking such as ABAB or ACAC in the normal stacking order of ABCABC. This change changes the local symmetry of the crystal structure and introduces additional lattice distortion. The presence of stacking faults will change the electronic band structure of the TNO crystal. Since the atomic arrangement in the stacking fault area is different from that in the surrounding area, the scattering and transmission behavior of electrons in these areas will also change. This may lead to changes in the bandgap width, the emergence of new electronic states or defective energy levels, thus affecting the electrochemical properties of TNO. At the same time, stacking faults may introduce additional carriers or change the carrier transmission path, thus affecting the electrochemical properties of TNO such as conductivity, carrier mobility and resistivity. This effect is of great significance for the development of new energy storage devices.
[0074] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A titanium niobate material rich in stacking fault defects, characterized in that: The crystal structure of the titanium niobate material contains at least one stacking fault defect, wherein an atomic layer is inserted into the normal crystal sequence of the titanium niobate material. The stacking order of the atomic layer is different from that of the remaining atomic layers, so that two inversely stacked layers appear at this position.
2. A method for preparing the stacking fault defect-rich titanium niobate material according to claim 1, characterized in that: include: Dissolving a titanium source and a niobium source in an organic solvent and stirring to obtain a mixed solution; heating the mixed solution to perform a solvothermal reaction to generate a precursor; The precursor is subjected to heat treatment and then quenching treatment to obtain a titanium niobate material with stacking faults; The heat treatment temperature is 600-1000°C and the time is 2-8h.
3. The method for preparing the stacking fault defect-rich titanium niobate material according to claim 2, characterized in that: The addition ratio of titanium source and niobium source is: the molar ratio of Ti to Nb is 1:(1.9-2.1), preferably 1:(1.95-2.05); Preferably, the titanium source includes one or more of titanium tetrachloride, butyl titanate and isopropyl titanate; Preferably, the niobium source includes one or more of niobium chloride and niobium oxalate.
4. The method for preparing the stacking fault defect-rich titanium niobate material according to claim 2, characterized in that: The organic solvent includes one or more of anhydrous ethanol, isopropanol, glycerol and ethylene glycol; preferably a mixed solvent of ethylene glycol and isopropanol.
5. The method for preparing the stacking fault defect-rich titanium niobate material according to claim 2, characterized in that: The reaction temperature of the solvent thermal reaction is 120-200°C, and the reaction time is 6-48h; preferably, the reaction temperature is 140-200°C, and the reaction time is 12-36h; Preferably, the heat treatment is calcination, and the heating rate is 3-10°C / min; preferably, the calcination temperature is 700-900°C, the calcination time is 4-6h, and the heating rate is 4-8°C / min.
6. The method for preparing the stacking fault defect-rich titanium niobate material according to claim 2, characterized in that: The precursor generated by the solvothermal reaction is washed and dried, and then heat treated; Preferably, the washing comprises one or more of suction filtration and centrifugation; Preferably, the drying temperature is 80-120° C. and the drying time is 12-48 hours.
7. The method for preparing the stacking fault defect-rich titanium niobate material according to claim 2, characterized in that: The quenching treatment is air quenching or liquid quenching; Preferably, the liquid quenching is to quickly add the precursor calcined to the highest temperature into a coolant for cooling; Preferably, the coolant used in the quenching treatment is air, distilled water, anhydrous ethanol or liquid nitrogen; preferably distilled water or liquid nitrogen; further preferably, the distilled water is liquid water at 0-25°C.
8. Use of the stacking fault defect-rich titanium niobate material according to claim 1 or the method for preparing the stacking fault defect-rich titanium niobate material according to any one of claims 2 to 7 in negative electrode materials for lithium-ion batteries.
9. A negative electrode for a lithium ion battery, characterized in that: The invention comprises a conductive substrate and the titanium niobate material rich in stacking fault defects as described in claim 1 or a titanium niobate material rich in stacking fault defects prepared by the preparation method of the titanium niobate material rich in stacking fault defects as described in any one of claims 2-7.
10. A lithium ion battery, characterized in that: The lithium-ion battery negative electrode comprises the negative electrode of claim 9.